Mapping Spaces as Factography: Human Traces and Negated Genres in Varlam Shalamov's Kolymskie rasskazy. (1st April 2013) - Young, Sarah J
Abstract : Taking as its starting point Shalamov's rejection of traditional literary genres for his writing of Gulag narratives, the article explores the author's engagement with, the 'literature of fact' movement from the 1920s onwards. Arguing that the spatial dimension of his Kolymskie rasskazy (Kolyma Tales) creates a conception of the documentary that takes his work beyond the original theory developed by the Left Front of Art ( LEF ), it proposes that the spaces between Shalamov's stories, and between the genres he negates, shape a textual parallel to the spatial form that the tales themselves advance. The motifs of surveying and mapping the region, and the connections made between writing and the movement of convicts through the landscape, centralize topography in the stories to fix the vanishing traces of prisoners and labour camps in the empty expanses of Kolyma's territory.